Transcriptomic Profiling at the Maternal-to-Zygotic Transition in Leech, Helobdella austinensis - Hsaio, Samuel; Saglam, Naim; Morrow, David; Shain, Daniel H. (Mdpi, 2024)
The glossiphoniid leech, Helobdella austinensis, is an experimentally tractable member of the superphylum, Lophotrochozoa. Its large embryonic cells, stereotyped asymmetric cell divisions and ex vivo development capabilities makes it a favorable model for studying the molecular and cellular events of a representative spiralian. In this study, we focused on a narrow developmental time window of similar to 6-8 h, comprising stages just prior to and immediately following zygote deposition. Employing RNA-Seq methodology, we identified differentially expressed transcripts at this fundamental ontogenic boundary, known as the maternal-to-zygotic transition (MZT). Gene expression changes were characterized by the massive degradation of maternal RNAs (similar to 45%) coupled with the rapid transcription of similar to 5000 zygotic genes (similar to 20% of the genome) in the first mitotic cell cycle. The latter transcripts encoded a mixture of cell maintenance and regulatory proteins that predictably influence downstream developmental events.
Keywords: glossiphoniid; development; maternal RNA; differential expression; fertilization